Selected Topics in Digital Business Systems Research: Editorial Introduction to Issue 30 of CSIMQ - Audrone Lupeikiene; Mubashrah Saddiqa (Complex Systems Informatics and Modeling Quarterly)
The 30th issue of CSIMQ includes four articles that cover research problems in the field of digital business systems. Two of the selected articles are systematic literature reviews, while the other two provide methodological additions to the theory. Systematic literature reviews focus on conceptual modeling for the digital business ecosystems development life cycle and on deep learning methods for retail sales forecasting. The other two articles discuss the methodological and technological aspects of the developing digital models of cyber-physical systems and of the solving heat loss calculation problem.